The effects of high-tech cameras on sports consumers' viewing experiences: the moderating role of sports involvement. Issue 1 (30th April 2021) - Jang, Wonseok (Eric); Kim, Young Jun; Chang, Kyungro; Kim, Taehee
Abstract : Purpose: Based on the limited-capacity model of motivated mediated message processing (LC4MP), this study aims to examine the effects of different camera types on the viewing experiences of sports consumers and their intention to follow social media channels, depending on their level of sports involvement. Design/methodology/approach: The design for this experiment utilized 2 (highly involved vs less involved sports consumers) × 2 (high-tech vs non-high-tech cameras) between-subjects design. Overall, 289 US-based sports consumers participated in this experiment. Findings: The results indicate that sports videos recorded by high-tech cameras lead to greater perceived novelty than those recorded by non-high-tech cameras, thus enhancing sports consumers' intention to follow social media channels, especially when consumers are highly involved with the target sports. However, sports consumers who are less involved with particular sports become distracted during their viewing experiences when high-tech cameras are used to broadcast games; these consumers' intentions to follow social media channels are not strengthened. Originality/value: Previous studies have focused mainly on the positive effects of high-tech cameras on the viewing experiences of sports consumers. Based on the LC4MP, the authors extend the existing literature not only by examining the mechanism that underpins the positive effects of high-tech cameras, but also by identifying a situation where the use of high-tech cameras results in a negative viewing experience for sports consumers.